Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
https://doi.org/10.13016/M2QR4NT6S
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Bad féministe - Gay, Roxane; Delvaux, Martine (Édito, 2018)
Section: 391 pages ; 23 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; cours; culture populaire; discipline; fem1000; fem3500; genre; identités LGBTQIA2+; lit2815; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; témoignage; états-unis; études littéraires